2018
DOI: 10.3390/s18051471
|View full text |Cite
|
Sign up to set email alerts
|

A Four-Feet Walking-Type Rotary Piezoelectric Actuator with Minute Step Motion

Abstract: A four-feet walking-type rotary piezoelectric actuator with minute step motion was proposed. The proposed actuator used the rectangular motions of four driving feet to push the rotor step-by-step; this operating principle was different with the previous non-resonant actuators using direct-driving, inertial-driving, and inchworm-type mechanisms. The mechanism of the proposed actuator was discussed in detail. Transient analyses were accomplished by ANSYS software to simulate the motion trajectory of the driving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Therefore, the common strategy between Li et al [ 11 ] and Ma et al [ 12 ] was to separately simulate the compliant mechanism and the driving mechanism (PM) of the system to indirectly obtain the desired output. As for PIM research in recent years, a four-foot rotary piezoelectric motor without a clamping mechanism was developed in Liu’s study [ 13 ], its transient simulation work took into account friction between the rotor and driving foot, but the key deformation mode of the PM and the abovementioned coupling problem were not reflected in the simulation. For the flexure mechanism + drive mechanism-type PIM research, such as Ma et al’s [ 12 ], Zhang et al [ 14 ] conducted stress and frequency analyses of the driving mechanism presented in a steady state simulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the common strategy between Li et al [ 11 ] and Ma et al [ 12 ] was to separately simulate the compliant mechanism and the driving mechanism (PM) of the system to indirectly obtain the desired output. As for PIM research in recent years, a four-foot rotary piezoelectric motor without a clamping mechanism was developed in Liu’s study [ 13 ], its transient simulation work took into account friction between the rotor and driving foot, but the key deformation mode of the PM and the abovementioned coupling problem were not reflected in the simulation. For the flexure mechanism + drive mechanism-type PIM research, such as Ma et al’s [ 12 ], Zhang et al [ 14 ] conducted stress and frequency analyses of the driving mechanism presented in a steady state simulation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the mechanical coupling between the PM and flexure mechanism or motor shaft was rarely reflected. Finally, the travel performance of the PIM was obtained by actual measurement or indirect formula calculation; it was not capable of being obtained directly from the simulation model [ 12 , 13 , 14 ]. However, for the motor design, the relationship between the specifications of the PM (i.e., type and size) and precision motor performance (i.e., driving force and travel) is what professional developers want to know most.…”
Section: Introductionmentioning
confidence: 99%
“…One of the areas is actuation. Because of their advantages of simple structure, flexible design, high resolution, and low power consumption, many piezoelectric actuators have been developed [11][12][13][14]. Actuators can be classified by vibration state into the resonant type and the non-resonant type.…”
Section: Introductionmentioning
confidence: 99%
“…Hunstig summarized the features of piezoelectric motors and discussed their applications and prospective [20]. Liu et al proposed a piezoelectric actuator using different bending vibration modes to perform linear or rotary motions [21][22][23]. Most recently, Lu et al demonstrated a disk-type inertial rotary motor with a no-load speed of 2200 r/min and stalling torque of 0.5 mN•m, which can be used for building a single shaft-type thruster to actuate a spherical underwater robot model moving at different operation patterns [24].…”
Section: Introductionmentioning
confidence: 99%